PENDAMPINGAN BALAS KOMENTAR DENGAN TEPAT, PRODUK LOKAL MAKIN DIKENAL: PANDUAN PRAKTIS KUB GRAHA PERMAI - Novita Novita; Rina Sundari (Jurnal Pengabdian Kompetitif, 2025)
Micro, Small, and Medium Enterprises (MSMEs) face increasingly fierce competition, particularly in terms of product marketing and customer interaction through social media. This community service activity aims to improve the ability of KUB Graha Permai members to utilize social media as a promotional tool and respond appropriately to customer comments to strengthen the image and appeal of the product. The target of the activity was 6 members of the Joint Business Group (KUB) Graha Permai who operate on a household scale. The activity was carried out on January 18, 2026, using training methods, demonstrations of promotional content creation practices, and simulations of responding to customer comments. The material provided included strategies for creating engaging content, tips for responding to positive and negative comments, and techniques for increasing interaction with potential customers. The results of the activity showed an increase in participants' knowledge and skills in utilizing social media effectively, including the ability to respond to customer comments professionally and communicatively. In addition, this activity encouraged digital entrepreneurship awareness and KUB members' interest in developing more creative promotional strategies. This community service activity contributed to expanding the product's market reach, increasing product value and image, and opening up opportunities for increasing MSME income sustainably through the use of social media.